Characterization of on‐orbit GPS transmit antenna patterns for space users. Issue 2 (16th June 2020) - Donaldson, Jennifer E.; Parker, Joel J.K.; Moreau, Michael C.; Highsmith, Dolan E.; Martzen, Philip D.
Abstract: The GPS Antenna Characterization Experiment (GPS ACE) has made extensive observations of GPS L1 signals received at geosynchronous (GEO) altitude, with the objective of developing comprehensive models of the signal levels and signal performance in the GPS transmit antenna side lobes. The GPS ACE architecture has been in place collecting observations with extreme sensitivity for several years, enabling the accumulation of full azimuthal coverage of the GPS transmit gain patterns over time. Results discussed in this paper include the reconstructed transmit gain patterns, with comparison with available preflight gain measurements from the GPS vehicle contractors. For GPS blocks with extensive ground measurements, the GPS ACE results show remarkable agreement. For blocks without extensive ground measurements, the GPS ACE results provide the only existing assessments of the full transmit gain patterns. The paper also includes results of pseudorange deviation analysis to assess systematic errors associated with GPS side‐lobe signals.